Efficacy of laparoscopic and trans-abdominal cerclage (TAC) in patients with cervical insufficiency: A systematic review and meta-analysis. (March 2022) - Marchand, Greg; Taher Masoud, Ahmed; Azadi, Ali; Govindan, Malini; Ware, Kelly; King, Alexa; Ruther, Stacy; Brazil, Giovanna; Ulibarri, Hollie; Parise, Julia; Arroyo, Amanda; Coriell, Catherine; et al.
Abstract: Background: Cervical insufficiency (CI) may result in preterm delivery. We sought out to perform this review and analysis to compare the efficacy of laparoscopic and open transabdominal cerclage (TAC) in patients suffering with CI. Methods: Our search included PubMed, Scopus, MEDLINE, ClinicalTrials.Gov, Cochrane and Web of Science. We analyzed the data with Open Meta-Analyst Software as well as Review Manager Software. We included observational and randomized controlled trials that included patients with CI that underwent laparoscopic cerclage or TAC. Results: We included a total of 43 studies. Laparoscopic and TAC had a positive effect by increasing gestational age (GA); for the laparoscopic group (mean deviation (MD)) = 14.86 weeks (W), 95% CI [10.67, 19.05], P  < 0.001) and TAC (MD = 12.79 W, 95% CI [10.97, 14.61], P  < 0.001). Furthermore, improvements in all outcomes assessed (total fetal survival rate, neonatal weight, and prevention of delivery at a gestational age of<24 weeks) were all significant with the exception of the prevention of all preterm deliveries<37 weeks; for both laparoscopic at (RR = 0.116, 95% CI [-0.006, 0.238], P  = 0.063) and TAC at (MD = 1, 95% CI [0.45, 2.24], P  = 1), and for prevention of deliveries<34 weeks for the laparoscopic group (RR = 0.446, 95% CI [-0.323, 1.215], P  = 0.256) only. Conclusions: Although limited data prevented pregnancy and prepregnancy subgroups as well as a head-to-head comparison, we still found that in patients suffering from CI, both TAC and laparoscopic approaches to cerclage revealed a positive effect in preserving the pregnancy.